The Effect of Problem-Based Learning Model on Students’ Learning Outcomes: A Case on Central Tendency Measures - Ainurrohimah, Syarifah; Hulukati, Evi P.; Irfah, Auli ((JIML) JOURNAL OF INNOVATIVE MATHEMATICS LEARNING, 2025)
This study investigates the low academic performance of eighth-grade students at SMP Negeri 2 Telaga, with an average score of 50.1. Effective learning requires the application of appropriate teaching models to foster active student participation and improve outcomes. The purpose of this research is to determine the difference in student achievement between those taught using the Problem-Based Learning (PBL) model and those taught through Direct Instruction, specifically on the topic of measures of central tendency. A quantitative approach was used with a Posttest-Only Control Group Design. The sample consisted of 16 students in the experimental group and 15 in the control group. Data were analyzed using both descriptive and inferential statistics. Descriptive analysis included measures such as mean, mode, median, variance, and standard deviation. Inferential analysis was conducted to test the normality and homogeneity of the data before performing hypothesis testing.The findings reveal that the average posttest score of students taught with the PBL model was higher than that of students taught using direct instruction. This difference was supported by a hypothesis test result of 555 at a 0.05 significance level and an effect size of 1.043, indicating a high level of impact.These results suggest that the Problem-Based Learning model significantly improves student learning outcomes in the topic of measures of central tendency for eighth-grade students at SMP Negeri 2 Telaga.